2020
DOI: 10.3389/fpsyg.2020.590181
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Robot Verbal Support on Human Team Members: Encouraging Outgroup Contributions and Suppressing Ingroup Supportive Behavior

Abstract: As teams of people increasingly incorporate robot members, it is essential to consider how a robot's actions may influence the team's social dynamics and interactions. In this work, we investigated the effects of verbal support from a robot (e.g., “good idea Salim,” “yeah”) on human team members' interactions related to psychological safety and inclusion. We conducted a between-subjects experiment (N = 39 groups, 117 participants) where the robot team member either (A) gave verbal support or (B) did not give v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, building on Strohkorb Sebo et al (2020) and Fraune et al (2019) , we argue that evaluating a robot’s effects on group dynamics also requires studying interactions in which participants are concerned with the consequences of this isolated interaction on their personal relationship on a long term, instead of strictly experimental data where no relationship is at stake for them. In our data, that the children are in the same school and will meet again is integral to their hesitations and attempts to make positive contact, which could have been completely different were they not meant to see each other again.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, building on Strohkorb Sebo et al (2020) and Fraune et al (2019) , we argue that evaluating a robot’s effects on group dynamics also requires studying interactions in which participants are concerned with the consequences of this isolated interaction on their personal relationship on a long term, instead of strictly experimental data where no relationship is at stake for them. In our data, that the children are in the same school and will meet again is integral to their hesitations and attempts to make positive contact, which could have been completely different were they not meant to see each other again.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Sebo et al (2020) attempted similar inclusion effects in groups of three participants comprising an outgroup member, playing a game. However, the robot provided verbal support, and while this was found effective in encouraging the outgroup member to participate, it also discharged ingroup members from making this sort of inclusive efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the context of a competitive game, participants have been shown to prefer and show fewer signs of aggression towards ingroup robots than outgroup humans [40,41]. Verbal support given by a robot to outgroup members seems to positively impact their participation in a joint task, but also reduces the verbal support given by other ingroup members [42]. In mixed group HRI, it has also been observed that the role and goalorientation played by the robot can influence interaction among humans and robots, and also among humans who are members of an in-group or out-group [43] (see Figure 4 for an example of research on this topic).…”
Section: Groups Of Humans and Robotsmentioning
confidence: 99%